The Influence of Tax Competition on Corporate Income Tax Rates and Tax Holidays in ASEAN-6 - Ratri Bening Pitaloka; Kuwat Slamet (Scientax: Jurnal Kajian Ilmiah Perpajakan Indonesia, 2025)
This research is motivated by the tax competition phenomenon, where countries compete to offer attractive tax policies to attract investors and boost national revenue. Two key instruments often employed are Corporate Income Tax (CIT) rate adjustments and tax incentives in the form of tax holidays. The purpose of this research is to analyse the impact of tax competition on CIT rates and tax holiday policies in six ASEAN countries: Indonesia, Malaysia, Thailand, Philippines, Singapore, and Vietnam. Over the past decade, most ASEAN-6 countries have reduced CIT rates and extended the maximum tax holiday period. This research employs a quantitative approach using regression coefficient tests, a reliability analysis model, and determination coefficient values. The findings reveal that tax competition has a positive impact on CIT rates and tax holidays in ASEAN-6. However, the effect on CIT rates is not significant, neither partial nor simultaneity effect. In contrast, tax competition significantly influences tax holiday policies, either a partial or a simultaneous effect. These findings are expected to provide insights into understanding the dynamics of tax competition and its implications for tax policy.